Molecular targets and approaches to restore autophagy and lysosomal capacity in neurodegenerative disorders. (December 2021) - Bastien, Julie; Menon, Suchithra; Messa, Mirko; Nyfeler, Beat
Abstract: Autophagy is a catabolic process that promotes cellular fitness by clearing aggregated protein species, pathogens and damaged organelles through lysosomal degradation. The autophagic process is particularly important in the nervous system where post-mitotic neurons rely heavily on protein and organelle quality control in order to maintain cellular health throughout the lifetime of the organism. Alterations of autophagy and lysosomal function are hallmarks of various neurodegenerative disorders. In this review, we conceptualize some of the mechanistic and genetic evidence pointing towards autophagy and lysosomal dysfunction as a causal driver of neurodegeneration. Furthermore, we discuss rate-limiting pathway nodes and potential approaches to restore pathway activity, from autophagy initiation, cargo sequestration to lysosomal capacity.